Setting Performance Targets - Stringer, Carolyn (Business Expert Press, 2012)
Ebook from IG Library ; Targets are an important part of our work life, whether we are setting them or meeting them. Target setting forms part of the budgeting process and the performance management of business units and individuals. Unfortunately the behavioral impacts of target setting on performance are not well understood, and this can lead to serious consequences such as game playing. Target setting is an under-researched area.